PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP OPINI AUDIT GOING CONCERN DENGAN AUDITOR SWITCHING DAN PRIOR OPINION SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013- 2016) - Putri, Azizah Dwiyana; Savitri, Enni; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research is aim to emprirically examines the influences of (1) profitability on going concern audit opinion, (2) liquidity on going concern audit opinion, (3) solvability on going concern audit opinion, (4) profitability on going concern audit opinion moderating by auditor switching, (5)liquidity on going concern audit opinion moderating by auditor switching, (6) solvability on going concern audit opinion moderating by auditor switching, (7) profitability on going concern audit opinion moderating by prior opinion, (8) liquidity on going concern audit opinion moderating by prior opinion, (9) solvability on going concern audit opinion moderating by prior opinion.The population is manufacturing companies on the Indonesian stock exchanges for the period 2013-2016. The sample method is purposive sampling with result of selection of 32 companies. The data was analyzed by logistic regression. The results of this study shows that the profitability and liquidity have an effect on the going concern audit opinion, whereas the solvability have no effect on the going concern opinion. Auditor switching was incapable of moderating the correlation of profitability, liquidity, and solvability on the going concern opinion. Prior opinion was capable of moderating the correlation of profitability on going concern audit opinion, but was incapable of moderating the correlation of liquidity and solvability on going concern audit opinionKeywords : Profitability, Liquidity, Solvability, Auditor Switching, Prior Opinion, Going Concern Audit Opinion.